Causes of Hypoglycemia in Hospitalized Diabetic Patients Referred to Endocrine Department of a Tertiary Level Hospital of India - K.C., Indu (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Diabetes mellitus (DM) results from relative deficiency or reduced effectiveness of endogenous insulin leading to both micro-vascular and macro-vascular complications. Treatment goal is intensive therapy as early as possible in patients with both type-1 and type-2 diabetes to bring the HbA1c to less than 7%. Occurrence of hypoglycemia in a diabetic patient is a common side effect of treatment. This study was aimed to find the causes of Hypoglycemia in diabetes patients. Methods: It was hospital based cross-sectional observational study on admitted diabetes patients with other co-morbid conditions who were on either oral hypoglycemic agents (OHA) or Insulin. Cause of hypoglycemia was elicited by history taking and analysis. Results: Out of 36 diabetics included in this study, seven had severe hypoglycemia, 22 had moderate to mild hypoglycemia. Most of them had various comorbidities. The causes of hypoglycemic episodes were varied. Conclusion: Hypoglycemia can occur despite cautious treatment protocol especially in diabetics with organ dysfunction, which can be prevented by alert and well-coordinated medical team.